ENHANCING DIGITAL MARKETING AWARENESS OF SMEs THROUGH PRODUCT PHOTOGRAPHY TRAINING: A BRIEF COMMUNITY SERVICE INITIATIVE - Wicaksono, Kuspuji (SEEIJ (Social Economics and Ecology International Journal), 2026)
The rapid advancement of digital technology presents both opportunities and challenges for Small and Medium Entreprises (SMEs). A key challenge is the limited expertise among SME owners in leveraging digital marketing, particularly in creating high-quality visual content. This community service initiative aimed to address this gap by providing practical training in product photography as a creative digital marketing strategy. The training involved 10 SME participants and covered fundamental digital marketing concepts, basic photography, and product photo-taking techniques. The evaluation results showed a significant improvement in participants’ understanding of the importance of product photography and their ability to produce professional-looking product photos. This initiative is expected to help SMEs enhance their competitiveness and sales effectively through digital marketing.